Fish oil–derived n–3 PUFA therapy increases muscle mass and function in healthy older adults(1) - Smith, Gordon I (Am J Clin Nutr, 2015)
Background: Age-associated declines in muscle mass and function are major risk factors for an impaired ability to carry out activities of daily living, falls, prolonged recovery time after hospitalization, and mortality in older adults. New strategies that can slow the age-related loss of muscle mass and function are needed to help older adults maintain adequate performance status to reduce these risks and maintain independence. Objective: We evaluated the efficacy of fish oil–derived n–3 (ω-3) PUFA therapy to slow the age-associated loss of muscle mass and function. Design: Sixty healthy 60–85-y-old men and women were randomly assigned to receive n–3 PUFA (n = 40) or corn oil (n = 20) therapy for 6 mo. Thigh muscle volume, handgrip strength, one-repetition maximum (1-RM) lower- and upper-body strength, and average power during isokinetic leg exercises were evaluated before and after treatment. Results: Forty-four subjects completed the study [29 subjects (73%) in the n–3 PUFA group; 15 subjects (75%) in the control group]. Compared with the control group, 6 mo of n–3 PUFA therapy increased thigh muscle volume (3.6%; 95% CI: 0.2%, 7.0%), handgrip strength (2.3 kg; 95% CI: 0.8, 3.7 kg), and 1-RM muscle strength (4.0%; 95% CI: 0.8%, 7.3%) (all P < 0.05) and tended to increase average isokinetic power (5.6%; 95% CI: −0.6%, 11.7%; P = 0.075). Conclusion: Fish oil–derived n–3 PUFA therapy slows the normal decline in muscle mass and function in older adults and should be considered a therapeutic approach for preventing sarcopenia and maintaining physical independence in older adults. This study was registered at clinicaltrials.gov as NCT01308957.